Effect of alcohol on the development of hepatocellular carcinoma in patients with hepatitis B virus-related cirrhosis: a cross-sectional case-control study - Kwon, Oh Sang (The Korean Association for the Study of the Liver, 2010)
BACKGROUND/AIMS: Whether alcohol intake increases the risk of hepatocellular carcinoma (HCC) in patients with chronic hepatitis B virus (HBV) infection remains controversial. The aim of this study was to determine the effect of alcohol intake on the development of HCC. METHODS: Between January 2006 and August 2008, 146 patients with an initial diagnosis of HCC who were hospitalized in 3 major hospitals in the Incheon area were enrolled as cases. Another 146 cirrhotic patients, who matched the cases by age and sex, were enrolled as controls. All cases and controls were HBsAg positive, and had a history of lifetime alcohol intake. RESULTS: The cases and controls were aged 53±8 and 53±9 years (mean±SD), respectively, with each group comprising 118 males and 28 females. The basal laboratory data, distribution of Child-Pugh class, HBeAg positivity (31.5% vs. 37.7%), HBV DNA level (5.74±2.35 vs. 5.98±2.29 log(10) copies/mL), and proportion with a lifetime alcohol intake of more than 292 kg (30.8% vs. 34.9%) did not differ between cases and controls. The cumulative alcohol intake and the proportion of heavy drinkers did not differ between the two groups in male patients. CONCLUSIONS: Alcohol intake might not increase the risk of HCC in patients with HBV infection.